(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
Tourism is a very important sector in Albania’s economy. With the promotion of tourist attractions, the number of foreign tourists has increased significantly. Language is of great importance for the communication of foreign tourists to tourist destinations. Today English is an international language and most tourist businesses require employees to speak English except the local language of the country. In this paper we will present a theoretical discussion on the importance and necessity of the English language in the development of the tourism sector from the point of view of tourist services providers and specifically hotel businesses. To fulfill the purpose of this search, the data collection was done by a self-administered questioner with closed thematic questions, with alternatives addressed to the service employees in tourism destinations in Durres, Shëngjin and Sarandë. The overall data collection of 250 questionnaires and total of 195 questionnaires were collected. Through descriptive analysis we have taken a picture of the characteristics of the monster in study according to the data of the structured questionnaire, respectively: Part 1 (socio-demographic characteristics), Part 2 (business stuff), (location and classification), Part 3 (language knowledge and opinion on its importance for employment in tourist businesses in Albania. The data was collected in January 2023. The article aims to highlight not only the most necessary language skills for tourism sector employees but also highlight the functions of English language use by employees of this sector, the most common problems they encounter in different skills, etc. The investigation and identification of such necessities puts the help of not only the employees of this sector but also the entrepreneurs of various tourist structures who can directly contribute to the improvement of their human resources employed as the motorcycle that sets in motion and guarantees financial income to their businesses thanks to professionalism